Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.jpcc.9b05355
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Impact of Alkali Li Metal Doped Mesoporous TiO2 Electron Transport Layer on the Performance of CH3NH3PbI3 Perovskite Solar Cells

Abstract: TiO 2 is most commonly employed as an electron transport layer (ETL) in mesoscopic n−i−p perovskite solar cells (PSCs). However, the low electron mobility, low electrical conductivity, and high electronic trap states of TiO 2 may have negative impacts on further enhancement of PSC performance. Metal doping is an efficient way to improve the electronic properties of TiO 2 films. In this work, we investigate the concentration-dependent impact of alkali lithium metal doping of the mesoporous TiO 2 ETL on the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…They reported that the carrier concentrations of undoped TiO 2 film increased from 4.93 × 10 9 to 6.43 × 10 10 cm −3 , and the resistivity of the undoped film decreased from 3.69 × 10 6 to 4.06 × 10 5 Ω cm after 5.0 mol% Li doping. Amalathas et al [ 13 ] investigated the influence of alkali Li‐doped on the electrical features of TiO 2 , which was utilized as an electron transport layer for perovskite solar cell application. They reported that the electrical conductivity of undoped TiO 2 increased from 4.39 × 10 −7 to 1.84 × 10 −6 mS cm −1 with 30 mg mL −1 Li doping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the carrier concentrations of undoped TiO 2 film increased from 4.93 × 10 9 to 6.43 × 10 10 cm −3 , and the resistivity of the undoped film decreased from 3.69 × 10 6 to 4.06 × 10 5 Ω cm after 5.0 mol% Li doping. Amalathas et al [ 13 ] investigated the influence of alkali Li‐doped on the electrical features of TiO 2 , which was utilized as an electron transport layer for perovskite solar cell application. They reported that the electrical conductivity of undoped TiO 2 increased from 4.39 × 10 −7 to 1.84 × 10 −6 mS cm −1 with 30 mg mL −1 Li doping.…”
Section: Resultsmentioning
confidence: 99%
“…According to the limited Li-doped TiO 2 films studies in the literature, Li doping is an effective way of increasing the conductivity of TiO 2 films. [10,11,13] Yan et al [10] have investigated the influence of Li doping on the crystal structure, and the optical and electrical features of TiO 2 thin films. They reported that the carrier concentrations of undoped TiO 2 film increased from 4.93 Â 10 9 to 6.43 Â 10 10 cm À3 , and the resistivity of the undoped film decreased from 3.69 Â 10 6 to 4.06 Â 10 5 Ω cm after 5.0 mol% Li doping.…”
Section: Electrical Properties Of Fabricated Photodiodesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that Li metal has been an effective additive to improve the electronic properties of electron transport layer (ETL) employed in perovskite solar cells. 212,213 Additionally, it is critical to promote the uniform electron transfer on the Li metal, the conductive host as well as the current collector with the aim to avoid the formation of dead Li.…”
Section: Electron Transportmentioning
confidence: 99%
“…[ 17 ] Peter et al doped mesoporous TiO 2 with alkali lithium metal to reduce the density of electron traps raised by oxygen vacancies in TiO 2 , and realized a reduced charge recombination at TiO 2 /perovskite interface. [ 18 ] Ma et al obtained a better contact at TiO 2 /perovskite interface by immersing TiO 2 into NaCl solution to passivate the trap states on the surface of TiO 2 , resulting in a better electronic transport properties. [ 19 ] Sidhik et al prepared Co‐doped mesoporous TiO 2 to passivate the electronic defect levels or space‐charge regions caused by oxygen vacancies in TiO 2 , and achieved faster electron transport and collection.…”
Section: Introductionmentioning
confidence: 99%